Vertrag gegen Gesetz und Lehre - Brauneder, Wilhelm (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
From the Middle Ages up to the 19th century Private Law (Civil Law) was dominated by different types of treaties and last wills – not by consuetudinary law or by statutory law. Roman Law (Gemeines Recht on the continent) was mostly not regarded as legal regulations but as a matter of opinions in the theoretical framework of legal scholars all over Europe. Because of this character, “Roman Law“ was not to be followed strictly, was discussed, even denied. Therefore the legal practice in everyday life – manifested in treaties, last wills and in different registers – followed by theoretical reflections about that together with the since 1500 increasingly referred to statutory laws enacted by the outspreading modern statehood stood against “Roman Law“ (Gemeines Recht). Private autonomy (Privatautonomie) prevailed.